Occurrence of N-Nitrosamines in the Pearl River delta of China: Characterization and evaluation of different sources. (1st November 2019) - Chen, Wenwen; Chen, Yingjie; Huang, Huanfang; Lu, Yijin; Khorram, Mahdi Safaei; Zhao, Wenyu; Wang, Dunqiu; Qi, Shihua; Jin, Biao; Zhang, Gan
Abstract: N -nitrosamines in water have drawn significant concerns for the health of water consumers due to their carcinogenic properties. N -nitrosamines are formed during disinfection of wastewater as well as different industrial and agricultural processes. This study characterized the N -nitrosamines compositions in eleven different wastewaters in the Pearl River Delta (PRD) in Southeast China, and the spatial distributions and the abundances of N -nitrosamines in the Pearl River water were detected. The results indicated that five N -nitrosamines species, including N -nitrosodimethylamine (NDMA), N- nitrosodiethylamine (NDEA), N -nitrosopyrrolidine (NPYR), N -nitrosomorpholine (NMOR) and N -nitrosodibutylamine (NDBA) were found in the industrial wastewater samples in the PRD. Remarkably high concentrations of NDMA (up to 4000 ng/L) were found in the wastewaters from the textile printing and dyeing as well as the electroplating, whereas NDMA, NDEA and NMOR were detected in the domestic wastewaters at concentrations lower than 15 ng/L. Moreover, we found that certain treatment processes for the electroplating wastewater could form a significant amount of NDMA, NPYR and NMOR. Analyses of the Pearl River water samples showed occurrences of different N -nitrosamines species, including NDMA (5.7 ng/L), NDEA (1.7 ng/L), NPYR (2.2 ng/L), NMOR (2.2 ng/L) and NDBA (4.9 ng/L). The abundances of N -nitrosamines species varied spatially due to the inputs from the different sources. Thus, our study provides unique and valuable information for occurrences, abundances and source characteristics of N -nitrosamines in the PRD. Graphical abstract: Image 1 Highlights: The different regional wastewaters are characterized according to N -nitrosamines compositions. Enrichment of certain N -nitrosamines species were found in the specific wastewaters. Uneven spatial distributions of N -nitrosamines species observed in the Pearl River of China.